(untitled) (Global Journal of Human-Social Science, 2017)
Modern Ethiopia with its borders and its dozens of nations nationalities and peoples came into being as a result of relentless campaigns of conquest which was accomplished by the Abyssinian state and its military might under Menelik by the late 19th century The subjugation of Shako peoples was part and parcel of this process By the conquest dozens of nations nationalities and peoples including Shako were subdued to the Amhara hegemony The historical experience of cultural and political domination economic exploitation and social discrimination under the Amhara dominated Ethiopian empire obviously caused the Shako people to start resistance Adopting the historical method of narrative and analysis and interrogating available primary and secondary sources on the subject this study argue that the patterns and natures of both domination power and resistance changes in historical time and space as they are not mutually exclusive The past offer us understanding in terms of contemporary new phenomenon which is still in its initial stage and thus contributing in increasing the historical awareness comprehend contemporary problems and impacts thereof